A study on adverse events following ChAdOx1 nCoV-19 CovishieldTM vaccination among beneficiaries at tertiary care centre, Hyderabad, India - Chajhlana, Sunil Pal Singh; Kanusali, Anjaiah; Manderwad, Guru Prasad; Allenki, Vineesh; Kamineni, Shashidhar (International Journal Of Community Medicine And Public Health, 2021)
Background: COVID-19 vaccine in present pandemic situation has been emerged as a blessing in disguise. Studies found to be associated with vaccine side-effects and it is an important factor that influences the confidence of vaccine uptake in general population. Present study was designed to provide an independent evidence on ChAdOx1 nCoV-19 vaccine side effects. Methods: A cross sectional study was conducted between January 2021 and February 2021 at our tertiary care centre among health care workers vaccinated using a validated questionnaire. Study subjects were contacted through phone to know about any adverse events following immunization for 0-24 hours, 24-48 hours and 48-72 hours. Data collected was entered and analysed with MS excel software 2007 and Epi info 3.5.3. Results: Healthcare workers participated were 1364. Majority of the symptoms following immunization were highest in age group of 18-28 years. Reported symptoms were pain at the site of injection- 619 (45.4%), fever- 423 (31%), Body pains- 318 (23.3%), headache- 189 (13.9%), tiredness- 142 (10.4%), swelling at the site of injection- 40 (2.9%), dizziness- 30 (2.2%), redness at the site of injection- 25 (1.8%), joint pains- 23 (1.7%), rash- 06 (0.4%), Breathlessness- 03 (0.2%) respectively. Conclusions: Overall results found the occurrence of side-effects which are in terms of manufacturer’s data and it has been noticed in young age. This study imparts the confidence for taking vaccination and further studies are required to minimize vaccine hesitancy (VH) and strengthen the public to boost their confidence in present vaccination drive.